The contribution of Niemann-Pick SMPD1 mutations to Parkinson disease in Ashkenazi Jews. Issue 9 (September 2015) - Dagan, E.; Schlesinger, I.; Ayoub, M.; Mory, A.; Nassar, M.; Kurolap, A.; Peretz-Aharon, J.; Gershoni-Baruch, R.
Abstract Introduction Parkinson disease is noted for its association with mutations in GBA and the p.G2019S mutation in LRRK2. This study aimed to evaluate the frequency of Ashkenazi founder mutations in sphingomyelin phosphodiesterase 1 (SMPD1) in Ashkenazi patients diagnosed with Parkinson's disease (PD); and their impact on PD phenotypic expression. SMPD1 underlies the lysosomal storage disease - Niemann-Pick. Methods A case (n = 287) control (n = 400) study was undertaken. All patients underwent a physical, neurobehavioral and neurologic examination that incorporated the Unified Parkinson's Disease Rating Scale. Three founder SMPD1 Ashkenazi mutations (c.996delC (fsP330), p.L302P and p.R496L) were investigated in patients and controls, previously evaluated for carriage of founder mutations in GBA and the p.G2019S mutation in LRRK2. Results Nine (3.1%) PD patients compared to two (0.5%) individuals from the control group were found to carry one of the three Ashkenazi SMPD1 founder mutations (p = 0.007). The overall clinical characteristics of PD patients carrying SMPD1 mutations were similar to those of PD patients with no mutations in SMPD1, GBA and LRRK2 (n = 189). Conclusion We maintain that disruptive mutations in SMPD1 constitute a risk factor for PD.